ETOS KERJA PRODUKTIF: ANALISIS KINERJA NABI DAUD DALAM AL-QURAN: UIN Sumatera Utara - Juliana Nasution (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2020)
Abstract Indonesian people productivity in general is still problematic and is often in the spotlight. Work productivity is an absolute prerequisite in developing the economy for increasing welfare. Muslim society as the majority of the Indonesian population needs to return to the guidance of the Quran that encourage people to cultivate productive work, as described by the Quran in Prophet Daud as a figure of productive workers. This article aims to study and describe the principles of Islamic work in the Quran with a case study of the performance of the Prophet Daud in verses 10 and 11 of the Saba` chapter. The results of this study show that the Prophet Daud worked productively, efficiently and effectively, by developing innovative attitude, working intensively, and maintaining work spirituality. The work ethic of the Prophet Daud required to be developed and implemented in the working world to increase work productivity. Keywords: Work Ethic, Productivity, Al-Quran, Prophet Daud